2004
DOI: 10.1086/425519
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Directed againstO‐Acetylated Sialoglycoconjugates Accelerate Complement Activation inLeishmania donovaniPromastigotes

Abstract: Anti-O-AcSGs were identified as an important source of CP activation under normal physiological conditions, suggesting that they play a role in conferring host protection against parasite infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…When serum from normal (NHS) and malaria patients (MS) were used as sources of complements separately, comparable C3-deposition in presence of CRP Mal was observed on RBC Mal being 92±2% and 90±6% respectively. This suggested undisturbed complement components in diseased state, as observed by our previous reports in other diseases [46][47]. Similar result was observed in presence of CRP-depleted patient's sera (91±5%).…”
Section: Crp Triggered Complement-cascade With Concomitant C3-depositionsupporting
confidence: 90%
See 1 more Smart Citation
“…When serum from normal (NHS) and malaria patients (MS) were used as sources of complements separately, comparable C3-deposition in presence of CRP Mal was observed on RBC Mal being 92±2% and 90±6% respectively. This suggested undisturbed complement components in diseased state, as observed by our previous reports in other diseases [46][47]. Similar result was observed in presence of CRP-depleted patient's sera (91±5%).…”
Section: Crp Triggered Complement-cascade With Concomitant C3-depositionsupporting
confidence: 90%
“…However, CRP is unable to trigger the alternate pathway [46]. As EGTA is known to trigger alternate pathway, C3-deposition through this pathways was measured, being only 23 ± 3%.…”
Section: Crp Triggered Complement-cascade With Concomitant C3-depositionmentioning
confidence: 92%
“…Previous studies by our group, using the preferential binding specificity of achatinin-H, have shown the expression on the cell surface of promastigotes of two specific 9-O-AcSGPs with molecular masses of 123 and 109 kDa (8,27). Concomitantly, enhanced anti-9-O-AcSGP-specific antibody responses against these parasite-specific sialoglycoproteins have been witnessed as a part of the host defense mechanism (5,6,10,39). Furthermore, these antibodies, as reported earlier, are leishmanicidal in activity; that is, they are capable of triggering the classical complement pathway, thereby causing Leishmania cell death (5).…”
Section: Discussionmentioning
confidence: 91%
“…Concomitantly, enhanced anti-9-O-AcSGP-specific antibody responses against these parasite-specific sialoglycoproteins have been witnessed as a part of the host defense mechanism (5,6,10,39). Furthermore, these antibodies, as reported earlier, are leishmanicidal in activity; that is, they are capable of triggering the classical complement pathway, thereby causing Leishmania cell death (5). Alternatively, several other 9-OAcSGPs have been documented on immune cells (65, 56, and 19 kDa) and erythrocytes (112, 107, 103, 57, 51, and 48 kDa) of VL patients (4,11,22).…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the kinetics of sialoglycoproteins binding by Achatinin-H, the lectin was iodinated with 125 I (Amersham Pharmacia Biotech, Sweden) by the chloramine T method [18] yielding a specific activity of 1.5×10 6 cpm/μg. For measuring the binding to cells, PBMC (2×10 6 /150 μL per tube) from five patients were suspended in 10 μL RPMI-1640 medium containing CaCl 2 (0.3 M) and bovine serum albumin (BSA, 0.2%), pH 7.2 (reaction buffer).…”
Section: Binding Assaysmentioning
confidence: 99%